The answer is (3,3). To solve this, first you write the system down.

x+3y=12

-4x+3y=-3

Next, you eliminate y by multiplying the bottom equation by negative 1.

x+3y=12

-1(-4x+3y=-3)

x+3y=12

-4x+3y=-3

Next, you eliminate y by multiplying the bottom equation by negative 1.

x+3y=12

-1(-4x+3y=-3)

Then, your answer is:

x+3y=12

4x-3y+3

Next, you combine like terms. Your answer is:

5x=15. (The y’s cancel out, because 3 is the opposite of negative 3.)

Divide both sides by 5, leaving you with x=3.

Lastly, you substitute x into the top equation. You get:

3+3y=12.

Subtract 3 from both sides, leaving you with 3y=9.

Divide both sides by 3, so y=3. The final answer is (3,3).